Social Media Marketing Dynamics Towards User Generated Content : A Qualitative Approach to Content Reach, Paid Advertising, Endorsements , and Hashtags at Dairyland On The Valley - Qonitah Berliana Salsabilla; Abdul Aziz (Indonesian Economic Review, 2026)
The development of social media has transformed tourism marketing strategies into participatory and experience-based communication. User Generated Content (UGC) plays a crucial role as it is perceived as more authentic and credible than official promotional content. This study aims to analyze the dynamics of social media marketing in encouraging UGC creation at Dairyland On The Valley, focusing on content reach, paid advertising, endorsements, and hashtag utilization. A qualitative case study approach was employed through in-depth interviews, observation, and social media content analysis. The findings reveal that content reach remains fluctuating and momentum-dependent. Paid advertising and endorsements increase visibility but have not effectively encouraged sustainable user participation. The official hashtags are not consistently used, limiting structured UGC aggregation. Supporting factors include the destination's visual appeal and interactive experience, while inhibiting factors include low user awareness and limited participatory strategies. The study concludes that social media marketing success depends not only on visibility but also on participatory integration strategies